Neuroendocrinology of a Male-Specific Pattern for Depression Linked to Alcohol Use Disorder and Suicidal Behavior - Walther, Andreas; Rice, Timothy; Kufert, Yael; Ehlert, Ulrike (Frontiers in Psychiatry, 2017)
Epidemiological studies show low rates of diagnosed depression in men compared to women. At the same time high rates of alcohol use disorders (AUDs) and completed suicide are found among men. These data suggest that a male specific pattern for depression may exist that is linked to AUDs and suicidal behavior. To date, no underlying neuroendocrine model for this specific pattern of male depression has been suggested. In this paper we integrate findings related to this specific pattern of depression with underlying steroid secretion patterns, polymorphisms, and methylation profiles of key genes in order to detail an original neuroendocrine model of male specific depression. Low circulating levels of sex steroids seem to increase the vulnerability for male depression, while concomitant high levels of glucocorticoids further intensify this vulnerability. Interactions of hypothalamus-pituitary-gonadal (HPG) and -adrenocortical (HPA) axis related hormones seem to be highly relevant for a male specific pattern of depression linked to AUDs and suicidal behavior. Moreover, genetic variants and the epigenetic profiles of the androgen receptor gene, well-known depression related genes, and HPA axis related genes were shown to further interact with men’s steroid secretion and thus may further contribute to the proposed male specific pattern for depression. This mini-review points out the multilevel interactions between the HPG and HPA axis for a male specific pattern of depression linked to AUDs and suicidal behavior. An integration of multilevel interactions within the three hit concept of vulnerability and resilience concludes the review.